Melatonin and methyl jasmonate-mediated morpho-physiological and biochemical adaptations to drought stress in French bean (Annals of Bangladesh Agriculture, 2025)
Although melatonin (MEL) and methyl jasmonate (MeJA) have been implicated for drought tolerance in plants, the effect of those has yet to be clarified in French bean. Therefore, the French bean plants were treated with exogenous MEL and MeJA under drought (D)-stress conditions to see their morphological and physiological alterations. The drought-stressed French bean plants treated with the combined application of MEL and MeJA showed partial recovery of root and shoot growth and pod yield. Total chlorophylls, carotenoids, and relative water contents were increased by 225.0 %, 109.6 % and 32.0 %, respectively in plants treated with D+ M 150 μM+ J 20 μM as compared to sole drought-stressed plants. Accumulation of osmolyte proline was also increased by 14.5 % in that combination. In contrast, the non-stress control plants showed the best performance in all the above-mentioned parameters. Percent electrolyte leakage (EL) was reduced by 266.0 % by the treatment combination of D+ M 150 μM+ J 20 μM, reflecting the combined role of MEL and MeJA in mitigating tissue damage caused by drought stress. However, the accumulation of flavonoids and phenolics was found to be reduced in drought-affected plants treated with MEL and MeJA that was comparable to non-stress control plants. The study suggests a collective role of MEL and MeJA in mitigating drought effects in French bean. Thus, the findings will contribute to sustainable growth of French bean in climate resilient agriculture.Ann. Bangladesh Agric. 28(2): 37-55